Language used by Egyptians on Facebook: a descriptive study, Sept. 2010- Sept. 2011 - Muhammed, Randa (AUC Knowledge Fountain, 2013)
This study investigates the language used by Egyptians online before, during and after January 25th revolution in Egypt. In that regard, the study explores top trends in Facebook status updates in the period between September 2010 and September 2011. It also looks at the writing script use at that specific time period. Finally, it presents a description of lexicon and deixis in the data. The study tries to answer the following research questions: 1- What are the top trends in Facebook status updates in the period between September 2010 and September 2011? 2- What is the most prominent writing script used during that specific time period? 3- What is the most salient representative of lexical entries and deixis in the data? Data in this study was completely a written one and consisted of a corpus of 500 status updates collected from 14 young Egyptian Facebook users. Data analysis reveals that the streamed status updates on Facebook at the time of the revolution are predominantly about politics; political discourse has governed the discussion among Egyptians since then. Meanwhile, it is found that Facebook statuses concerning social relations and religion had topped the discussion before the revolution began. The analysis also shows a widespread use of Arabic script employed in the update status feature. The dominance of this trend in writing might be related either to the type of topics discussed there or to the need to produce a clear and comprehensible message at that time. As for lexicon use, the results indicate that the most salient representative of lexical items is collocation. Moreover, it is found that the pronoun “?ihna", the demonstrative “da", and the word “in-nahrda" are the most prominent representatives of pronoun, place, and time deixis respectively. The study examines language use in relation to wider social trends such as identity and political change.